Electrical transport properties of Pr1-xSrxMnO 3 (x = 0 to 045) - Ewe L.S.; Abd-Shukor R. (2023)
The electrical transport properties of polycrystalline Pr 1-xSrxMnO3 (x = 0 to 045) perovskite manganites prepared by the solid state reaction method have been studied. The insulator-metal transition temperature Tim shifted to higher temperatures when Sr content was increased. Generally, the average grain size decreased with increase in Sr content. The resistivity versus temperature curves in the metallic (ferromagnetic) and insulating (paramagnetic) region were fitted with several models. The activation energy of electrons hopping and the density of states at the Fermi level were estimated from the curve fitting. The ?-T2 curve was found to be nearly linear in the metallic region, but the ?-T25 curve deviated from linearity for x = 02 and 033. The variable range hopping model and small polaron hopping models fit well in the high temperature region. Sr substitution led to the decrease in the activation energy and the To values. 2010 Institute of Materials, Minerals and Mining.